2008
DOI: 10.1007/s11060-008-9712-4
|View full text |Cite
|
Sign up to set email alerts
|

Early relapses in primary CNS lymphoma after response to polychemotherapy without intraventricular treatment: results of a phase II study

Abstract: and 5) and cytarabine (Ara-C; cycles 3,6) based systemic therapy including dexamethasone, vinca-alkaloids, ifosfamide and cyclophosphamide.Results: Study accrual was prematurely stopped in 11/05 due to a high rate of early relapses.Seventeen/18 patients were assessable for response: Nine (53%) achieved complete response (CR), two (12%) complete response/unconfirmed (CRu), two (12%) partial response (PR), four (24%) showed progressive disease (PD); one treatment was stopped due to toxicity.Median follow-up is 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 29 publications
0
45
2
2
Order By: Relevance
“…Here, the Bonn group reported early relapses and a median duration of response of ten months in younger patients (median age 53, range 27-59 years), who did not receive intraventricular treatment, but otherwise the same systemic therapy as in the original Bonn regimen, arguing for the need of CSF-targeted therapy. 22 While the collective experience from the two Bonn studies 7,22 indicates the need for intraventricular treatment, two retrospective analyses did not find that intrathecal chemotherapy had any impact on survival. 23,24 Moreover, Omuro et al 25 reported disappointing results of a retrospective study of 64 patients with a median age of 47 years who had a median PFS of 12 months only, despite the fact that intrathecal treatment consisting of the same agents (MTX, AraC and methylprednisolone) was part of both the induction treatment and a maintenance phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the Bonn group reported early relapses and a median duration of response of ten months in younger patients (median age 53, range 27-59 years), who did not receive intraventricular treatment, but otherwise the same systemic therapy as in the original Bonn regimen, arguing for the need of CSF-targeted therapy. 22 While the collective experience from the two Bonn studies 7,22 indicates the need for intraventricular treatment, two retrospective analyses did not find that intrathecal chemotherapy had any impact on survival. 23,24 Moreover, Omuro et al 25 reported disappointing results of a retrospective study of 64 patients with a median age of 47 years who had a median PFS of 12 months only, despite the fact that intrathecal treatment consisting of the same agents (MTX, AraC and methylprednisolone) was part of both the induction treatment and a maintenance phase.…”
Section: Discussionmentioning
confidence: 99%
“…This was also the case in the Bonn regimen when given without intraventricular therapy. 22 In comparison, intraventricular MTX, AraC and methylprednisolone was delivered during all six induction chemotherapy courses in the original Bonn regimen using the same systemic HD-MTX schedule, thus avoiding a 6-week period of no MTX delivery. Theoretically, the inferior results of the Bonn regimen without intraventricular treatment, as well as the results in the present study as compared to the original Bonn regimen, could be due to lymphoma growth or leptomeningeal seeding during the time when the tumor was not exposed to MTX.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors recently reported a higher rate of early relapse after eliminating intraventricular chemotherapy from their initial protocol despite the use of high-dose i.v. MTX (5 g/m 2 ) (modified Bonn protocol) [80]. The role of intrathecal prophylaxis warrants investigation in a prospective trial.…”
Section: Treatment Of Newly Diagnosed Pcnslmentioning
confidence: 99%
“…Therefore, intrathecal therapy is not considered as a standard of care which is supported by 2 retrospective analyses suggesting that additional intrathecal treatment does not result in prolonged OS compared to patient cohorts that were not treated intrathecally [60,61]. In contrast, very promising results of a trial using a polychemotherapy approach including intraventricular therapy with MTX, prednisolone, and cytarabine were not reproduced when the intrathecal treatment was omitted [62][63][64].…”
Section: Intrathecal Therapymentioning
confidence: 99%